GATT ARTICLE XX AND INTERNATIONAL TRADE: A WINDOW FOR ACHIEVING FOOD SECURITY - Gupta, Shipra (International Journal of Psychosocial Rehabilitation, 2020)
In this ever changing world where the international community have ability to deal with every problem, foreseeable or not, we are still lagging behind in dealing with world food problem, which is one of the greatest challenges faced by the global community. This essay aims to shed light on the Article XX of GATT which provides exceptions as a window through which right to food can be applied in WTO disputes concerning food security, by focusing on international trade as being helpful in achieving food security. While there have been no disputes regarding food security and expressly invoking right to food, much can be deduced from WTO jurisprudence. The researcher aims to achieve the objective of the essay by analyzing the documents and data already published by the verified sources.